Experimental Study on Permeability and Deformation Characteristics of Bedding Shale under Triaxial Shear-Seepage Coupling - Zhinan Lin; Shihong Feng; Jiaquan Wang; Qiang Zhang; Haifeng Long; Guangming Chen (Geofluids)
The bedding structure of shale is generated during the deposition and formation, which results in shales with prominent anisotropic characteristics. It depends on stability, control of oil and gas storage, and deep exploitation. In addition, the mechanical and permeability parts of bedding shale are very complex when it is under deep underground space with coupled high stress and high seepage. In this study, the black bedding shale was used as the research object, and a series of triaxial shear-seepage coupling tests were carried out. Firstly, the triaxial shear stress-shear strain curves and permeability-shear stress curves of different bedding shales under other triaxial shear-seepage coupling conditions were obtained. Secondly, the failure characteristics and shear deformation characteristics of shale under the shear-seepage coupling effect were explored. The shear stress threshold and permeability evolution law at each stage of shear failure were discussed. Thirdly, the shear strength, failure mode, and mechanism parameters of the black bedding shale under different normal stress and seepage pressure were studied. Fourthly, the linear M-C criterion, Ramamurthy criterion, and Hoek-Brown criterion characterize the variation of damage strength of shale with bedding orientation under triaxial shear-seepage coupling. Those results provide an experimental basis for exploring the anisotropic mechanical characteristics and failure mechanism of bedding shale under shear-seepage coupling.